Study of corrosion resistance of laser welded Au-Pd-Ag-In alloy using electrochemical. - Santos, Marcio Luiz dos; Acciari, Heloísa Andréa; Riccardi, Carla dos Santos; Guastaldi, Antonio Carlos [UNESP] (My University, 2011)
The aim of this work was to evaluate the corrosion resistance of AuPdAgIn alloy, submitted to laser beam welding, in 0.9% NaCl solution, using electrochemical techniques. Measures of the open circuit potential (OCP) versus time were applied to electrochemical experiments, as well as potentiodynamic direct scanning (PDS) and electrochemical impedance spectroscopy (EIS) on AuPdAgIn alloy, submitted to laser beam welding in 0.9% NaCl solution. Some differences observed in the microstructure can explain the results obtained for corrosion potential, Ecorr, and corrosion resistance, Rp. EIS spectra have been characterized by distorted capacitive components, presenting linear impedance at low frequencies, including a non-uniform diffusion. The area of the laser weld presented corrosion potential slightly superior when compared to the one of the base metal. The impedance results suggest the best resistant corrosion behavior for laser weld than base metal region. This welding process is a promising alternative to dental prostheses casting.
Keywords: Laser Welding; Corrosion; Au-Pd-Ag-In; Electrochemical Techniques